2001
DOI: 10.1143/jjap.40.1013
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Ion Beams Produced in a Plasma Focus Device

Abstract: The characteristics of the ion beams produced in a plasma focus device were studied. In the experiment, a Mather-type plasma focus device was used which was prefilled with H 2 at 2.3 Torr. Ion species and their energy spectra were evaluated with a Thomson parabola spectrometer. The particle pinhole image was obtained with an aluminum filtered particle pinhole camera. The ion current density was measured with a biased ion collector. From the measurement, the proton beam energy was found to be distributed from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…[1][2][3] The mechanism leading to the generation of the high energy ion beam is believed to be closely corelated to phenomena that give rise to localised high electric field, such as the rapid compression during the radial pinch phase and instability. In fact, from the measurements of electron beam, 4) there is indication that localised high electric field may be induced by both these two phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The mechanism leading to the generation of the high energy ion beam is believed to be closely corelated to phenomena that give rise to localised high electric field, such as the rapid compression during the radial pinch phase and instability. In fact, from the measurements of electron beam, 4) there is indication that localised high electric field may be induced by both these two phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…39 While studying the characteristics of the hydrogen ion beam, Takao et al observed that the energy spectrum of the proton is distributed from a value in between 150 keV and 2 MeV. 21 In this experiment, we could detect much lower energy ions ͑Ն10 keV͒ as compared to the previous reports. It is evident from Fig.…”
Section: -3mentioning
confidence: 57%
“…the characteristics of hydrogen ion beam emission from a PF device and they observed that the proton beam energy is distributed from 0.15 to 2 MeV. 21 The angular distributions of the ion beam emission from the PF device with different experimental conditions were also investigated to some extent. Kelly and Marquez 22 found, while investigating the ion emission from a 5 kJ PF device, that the measured ion number at 0°͑anode axis͒ direction is approximately twice of that at 90°direction.…”
Section: Introductionmentioning
confidence: 99%
“…However, the physical mechanism of the production of these ions remains unclear. These energetic ions are considered to play an important role in the production of the intense neutron flux in the plasma focus device when using deuterium gas [4]. In addition, these ions are anticipated for application as an intense pulsed ion source.…”
Section: Introductionmentioning
confidence: 99%
“…In general, SSNTDs seem to be particularly suitable for time-integrated experimental studies of different nuclear reaction products, such as 3 He and 4 He nuclei, protons, fast neutrons and heavy impurity ions. Fast neutrons can be detected with the polycarbonate CR-39 (C 12 H 18 O 7 ) through the tracks of recoil protons originating in the detector material itself, or in radiator foils such as polyethylene placed in front.…”
Section: Introductionmentioning
confidence: 99%